PROFIL PENGGUNAAN ANTIKOAGULAN PADA PASIEN COVID-19 DI IRNA FATMAWATI RSUD DR M YUNUS BENGKULU - Bella Donna Perdana Putra; Budi Suprapti; Arina Deri Puspita Sari; Mulya Sundari (JURNAL MEDIA KESEHATAN, 2022)
Problems: COVID-19 is a respiratory infection disease caused by SARS-CoV-2. This disease can be transmitted to humans and has spread globally. One of the complication that accompanies COVID-19 is the occurrence of coagulopathy, therefore anticoagulants are used in the treatment of COVID-19. However, studies or reports on the use of anticoagulants in COVID-19 patients have never been carried out by the Research and Development Agency of the Ministry Health Republic Indonesia. The aim of the research: To determine the profile of the use of anticoagulants in COVID-19 patients being treated at IRNA Fatmawati RSUD Dr. M Yunus Bengkulu. Research method: This study is a descriptive observational study with retrospective data collection using a time limited sampling technique, where the data is taken from the medical records of COVID-19 patients being treated at IRNA Fatmawati RSUD Dr M Yunus Bengkulu and met the inclusion criteria in the April 2020December 2021 period. The results: In this study, 258 medical records of COVID-19 patients met the inclusion criteria, with a greater proportion of male (58.1%) than female (41.9%). The greatest use of anticoagulants was at the age of 56-65 years reaching 37.6%. Fondaparinux was the most widely used anticoagulant (51.2%) followed by heparin (36.8%) and enoxaparin (12.1%). Conclusions: Men aged 56-65 years are more at risk of infection with COVID-19 and coagulopathy complications that require the use of anticoagulants. Keywords: Anticoagulants, Covid-19, Bengkulu Hospital